Hyperbaric oxygen therapy as a neuromodulatory technique: a review of the recent evidence - Bin-Alamer, Othman; Abou-Al-Shaar, Hussam; Efrati, Shai; Hadanny, Amir; Beckman, Robert L.; Elamir, Mohammed; Sussman, Elliot; Maroon, Joseph C. (Frontiers in Neurology, 2024)
Hyperbaric oxygen therapy (HBOT) has recently emerged as a promising neuromodulatory modality for treating several neurological and psychological disorders. Various studies indicate that HBOT can promote brain recovery and neuroplasticity through the modulation of key cellular and molecular mechanisms. HBOT affects multiple primary pathways and cellular functions including mitochondrial biogenesis and function (increased Bcl-2, reduced Bax, and enhanced ATP production), neurogenesis (upregulation of Wnt-3 and VEGF/ERK signaling), synaptogenesis (elevated GAP43 and synaptophysin expression), and anti-inflammatory responses (reduced TNF-α and IL-6). These mechanisms contribute to significant clinical benefits, such as enhanced cognitive function, improved recovery from traumatic brain injury and post-concussion syndrome, and symptom reduction in conditions like post-traumatic stress disorder and fibromyalgia. By influencing these molecular targets, HBOT offers a novel approach to neuromodulation that warrants further exploration. This review discusses the representative mechanisms of action of HBOT and highlights its therapeutic neuromodulatory effects and potential clinical applications across various neurological and psychiatric conditions.